The Johan Bergh Historia Award Recipients (Historia, 2021)
Historia congratulates the following History students on being the top achievers in third year at their respective institutions for 2017. In recognition of this achievement, each student receives a year’s subscription to Historia.
Keywords: The Johan Bergh Historia Award Recipients